if x3 + 3x2 - 9x  + c is of the form (x-a)2(x-b) then find c

Dear Student,
Please find below the solution to the asked query:

x3+3x2+9x+c=0a and c are roots of the equation.Sum of roots=a+a+b=-312a+b=-3b=-3-2a=-3+2aSum of roots taking two at a time we geta2+ab+ab=91a2+2ab=-9a2-2a3+2a=9a2-6a-4a2=93a2+6a+9=0Divide each term by 3a2+2a+1=0a+12=0a=-1b=-3+2a=-3-2=-1Product of roots=-c1-1×-1×-1=-cc=1

Hope this information will clear your doubts about this topic.

If you have any doubts just ask here on the ask and answer forum and our experts will try to help you out as soon as possible.

  • -33
where a and b are its roots
  • 3
What are you looking for?